7.0k views
4 votes
Please solve in a timely manner. Previous tutor disconnected. Explanation not needed just a brief answer thank you for your time.

Please solve in a timely manner. Previous tutor disconnected. Explanation not needed-example-1

1 Answer

5 votes

Step 1; Write the two functions.


\begin{gathered} f(x)\text{ = x + 6} \\ g(x)\text{ = 2x + 6} \end{gathered}

Step 2: Answer each question separately


a)\text{ (f - g)(}x)

Next, In the question a, you are to subtract g(x) from f(x).


\begin{gathered} (f\text{ - g)(x) = f(x) - g(x)} \\ =\text{ x + 6 - (2x + 6)} \\ =\text{ x + 6 - 2x - 6} \\ \text{Collect similar terms} \\ =\text{ x - 2x + 6 }-\text{ 6} \\ =\text{ -x} \end{gathered}

(f - g)(x) = -x

Step 3:

b)


undefined

User Sonia Maklouf
by
5.8k points